Environmentalist - Stidworthy, John (New York Gloucester Press, 1992)
Encourages the reader to examine the relationship between humans and the environment and to consider certain ecological problems. Includes projects.
"A Watts/Gloucester library edition"--p. 4 of cover.
Keywords: Human ecology -- Juvenile literature; Ecology -- Juvenile literature; Ecology; Environmental education -- Activity programs -- Juvenile literature; Environmental protection -- Juvenile literature; Environmental protection; Human ecology